How to position anewhigh-end sportswear brand, recto verso sports,within the new paradigm of the luxury fashion market - Decavel, Fien Toon Terry (2021)
This dissertation revolves around the new paradigm of the luxury fashion market which is the consequence of the rising athleisure trend through an increasing cross-sector convergence between sportswear brands and luxury fashion. (Woodworth, 2018)Athleisure is the fastest growing clothing category in fashion (Allied Market Research, 2019)and can be defined as “casual clothing designed to be worn both for exercising and for general use”. (Merriam Webster, 2019)Recto Verso Sports is a new Belgian high-end sportswear brand tapping intothe rising athleisure trend by offering a collection that covers multiple categories being sportswear, athleisure wear and fashion. As a newcomer in this highly competitive market and because of operating in different categories of the fashion industry, Recto Verso facesdifficulties in finding the right positioning for the brand.Therefore, the goal of this work project is to answer the following research question ‘How to position a new high-end sportswear brand Recto Verso Sportswithin the new paradigm of the luxury fashion market’. First, literature research was conducted followed by qualitative market research through in-depth interviews and focus groups. This research shows thatthe growth of athleisure is driven by wellness aspirations, celebrity endorsement on social media(Woodworth, 2018)and a search for comfortable yet fashionable (luxury) clothing. Furthermore, collaborative capsule collections are the expression of sportswear brands going moreand moreinto luxury fashion and vice versa, contributingto the rising luxury athleisure trend. (BCG-Altagamma, 2019)Luxury athleisure is considered a fashion statement delivering both substance and status and is generally not used to conduct sports. Recto Verso shouldpositionitselfas a luxury sportswear/athleisure brand that also delivers status next to the substance it already delivers through its superior quality and comfort.